Papua New Guinea food price bulletin: January 2023 - International Food Policy Research Institute; Kedir Jemal, Mekamu; Schmidt, Emily (International Food Policy Research Institute, 2023)
Users can download time series food price data, and build graphs and tables for over 20 different food crops at our food price database webpage: https://www.ifpri.org/project/freshfood-price-analysis-papua-newguinea. The average (nominal) price of staple foods in Port Moresby was 22 percent less (in nominal terms) in the 4th quarter of 2022 compared to quarter 4 of 2021. The 2022 quarter 4 price of sweet potato and taro in Kokopo was 22 percent greater compared to the same quarter in 2021. In addition green leafy vegetables price increased, in part due to unseasonably dry weather in East New Britain. Despite a rising global food price trend in 2022 as a result of the Russia-Ukraine crisis, increasing fuel prices, and weather stress, the price of imported rice in PNG remains relatively stable, with an average annual (nominal) price variation of 10 percent across 4 markets. In December 2022 a kilo of rice (Roots rice) cost 4.03 PGK/kg, compared to 5.07 PGK/kg in Port Moresby.